Evaluasi Kinerja Struktur Jembatan Terhadap Beban Gempa Berdasarkan Analisis Dinamik Dan Ketentuan SNI Terbaru - Masarrah (CV. SINAR HOWUHOWU, 2026)
The construction industry significantly contributes to global carbon emissions due to the extensive use of Portland cement. One approach to reducing environmental impacts is the development of eco-friendly concrete by utilizing industrial waste materials such as fly ash and slag as partial cement replacements. This study aims to analyze the performance of fly ash- and slag-based eco-friendly concrete in terms of compressive strength and durability. An experimental laboratory method was employed using several concrete mix variations, including normal concrete, fly ash concrete, slag concrete, and their combined mixture. Compressive strength tests were conducted at 7, 14, and 28 days, while durability was evaluated through water absorption and porosity tests. The results indicate that concrete containing fly ash and slag exhibits slower strength development at early ages; however, at 28 days, it achieves comparable or higher compressive strength than normal concrete. In terms of durability, eco-friendly concrete shows lower water absorption and porosity values, indicating a denser microstructure and better resistance to aggressive environmental exposure. Therefore, fly ash- and slag-based concrete has strong potential as a sustainable construction material.